When Policy and Infrastructure Provisions are Exemplary but still Insufficient: Paradoxes Affecting Education for Sustainability (EfS) in a Custom-designed Sustainability School - Kuzich, Sonja; Taylor, Elisabeth; Taylor, P. (2015)
Schools willing to implement education for sustainability (EfS) commonly find themselves confronted with curricula, school grounds and buildings and teaching practices that do not lend themselves easily to best practice EfS. In this article, we present what we learned about some of the challenges confronted daily by the staff of a purpose-built sustainability primary school situated in a ‘green’ suburb in Western Australia. Over the period of a year, we regularly engaged with the staff of the school through semi-structured, in-depth interviews and classroom observations as part of an interpretive ethnographic study. We identified three key themes—policy infrastructure, physical infrastructure and pedagogical infrastructure—that serve as both affordances and counter-affordances to best practice EfS. Given the paradoxical interplay of the affordances and counter-affordances shaping the school’s implementation of EfS, we suggest that overcoming these paradoxes requires no less than a transformation of school culture.